Hindī ke sāmantī cetanā paraka upanyāsa : Yādavendra Śarmā "Candra" ke upanyāsoṃ ke sandarbha meṃ - Śarmā, Devadatta (Viveka Pabiśiṅga Hausa, 1977)
Study on the traditional aristocratic ideology in Hindi fiction, with special reference to the novels of Yadavendra, Sharma, b. 1932.